Social representations of socioenvironmental dynamics in extractive ecosystems and conservation practices with sustainable development: a bibliometric analysis - Zárate-Rueda, Ruth; Beltrán-Villamizar, Yolima Ivonne; Murallas-Sánchez, Daniella (Environment, development and sustainability, 2021)
Social representations necessarily originate from the interaction between individuals and groups in a social setting through communication and shared knowledge; thus, imaginaries, sensations, meanings and concepts emerge, with which subjects may understand the world from their everyday lives. Concurrently, changes introduced in diverse ecosystems yield to permanent transformations in the use of land and its preservation by the entities regulating them and the communities inhabiting them. Thus, this study is focused on social representations of socioenvironmental dynamics in extractive ecosystems and conservation practices with sustainable development, built by individuals and groups coexisting in environmental areas under special protection. To understand the current status of the subject matter, a bibliometric analysis was carried out, given that it is a pertinent methodology to identify the scientific production, impact and trajectory of the area of knowledge in a scientific context. By means of the VOSviewer software, a scientific mapping was built to visualize co-occurrence, co-authoring and co-citation networks, in order to analyze the clusters that substantiate research trends regarding the emergent domains in the subject matter. This document closes with a discussion regarding the influence of the social representations of rural communities related to their territories, in order to foster sustainable participative conservation practices.